Peningkatan Kemampuan Sosial Emosional Siswa Melalui Model Pembelajaran Role Playing Siswa Kelas X-7 di SMAN 13 Medan - Armiza, Destri; Kesuma, Sapta; Muslim, Yusnita (Universitas Pahlawan Tuanku Tambusai, 2024)
This research was conducted to improve the Social Emotional Ability of Students through Role Playing Learning Model of Class X-7 Students at SMAN 13 Medan. The type of research determined in this study is Classroom Action Research (PTK). The research subjects were students of class X-7 SMAN 13 Medan which amounted to 36 students. The method used is qualitative descriptive analysis. At the time of the analysis, the data obtained on the improvement of social-emotional abilities amounted to 55% of the Developing As Expected category. In cycle II, it reached 80% of the Very Well Developed category. Thus the data obtained in cycle II, this research was achieved so it was concluded that there was an increase in students' social emotional abilities through the Role Playing model of class X-7 students at SMAN 13 Medan.